A biogeographical history and timeline for the evolution of Australian snapping turtles (Elseya: Chelidae) in Australia and New Guinea. (23rd December 2013) - Todd, Erica V.; Blair, David; Georges, Arthur; Lukoschek, Vimoksalehi; Jerry, Dean R.; Gillman, Len N.
Abstract Aim Our aim was to investigate the evolutionary response of a freshwater Gondwanan relictual lineage to ongoing aridification of the Australian landmass. Australian snapping turtles (Elseya spp.) are riverine specialist species and were used to examine biogeographical hypotheses associated with changes to riverine connectivity through eustatic sea‐level change, landform development and aridity across this understudied region. Location Northern and Eastern Australia and New Guinea. Methods Phylogenetic relationships were inferred for all extant species of Elseya plus two putative species not yet described, from molecular data comprising mitochondrial (control region, ND4 and 16S) and nuclear (R35 intron) loci, using maximum likelihood and Bayesian inference methods. A calibrated relaxed molecular clock was used to estimate divergence times. Intraspecific lineage structure and diversity were investigated using control region sequences analysed via haplotype networks and AMOVA. Results Elseya species exhibited a striking degree of local endemism across their range. Four divergent clades corresponded geographically to New Guinea, southern New Guinea plus northern Australia, north‐eastern Australia, and south‐eastern Australia. These arose in the late Miocene (c. 5.82–9.7 Ma), diversifying further in the early Pleistocene (c. 2.2–2.43 Ma and 1.36–1.66 Ma), coincident with major phases of aridity and climatic upheaval. Main conclusions The genus Elseya has a long vicariant history in Australia, closely tied to disconnection of fluvial habitat through landform evolution, sea‐level rise and ongoing aridification. Our analysis paints a more complete picture of Australian freshwater biogeography, including evidence for periodic connectivity with New Guinea, important regional biogeographical barriers, and the location of potential freshwater refugia. Congruence with patterns described for terrestrial groups implies a collective response of the Australian fauna to aridification.